Case 3841: Epigraphiidae Guenée, 1845 (Lepidoptera, Gelechioidea): proposed suppression to conserve the widely used family group name Depressariidae Meyrick, 1883. - Nieukerken, Erik J van; Karsholt, Ole; Brown, Richard L; Heikkilä, Maria; Huemer, Peter; Kaila, Lauri; Landry, Jean-François; Li, Houhun; Ponomarenko, Margarita G; Sinev, Sergey (Bulletin of Zoological Nomenclature)
Noticed in BZN 78 (30 Apr 2021): 2.